Impact of different frequencies in the entrapment of bacterial pathogens from drinking water using dielectrophoretic phenomena - Sankaranarayanan, A.; Prabu Sankarlal, K.M.; Raja, D. (Химия и технология воды, 2016)
The article has investigated the removal of water borne pathogens using dielectrophoresis (DEP) filter which is energized by varying the frequency of the applied potential from 10 kHz to 2 MHz with different voltage levels of 5; 10; 15 and 20 V. Separate experiments are conducted in artificially contaminated water samples with Escherichia coli, Staphylococcus aureus and Vibrio cholera up to 2 h. The impact of signal frequency and voltages on DEP based water treatment system has been analyzed statistically. Results have demonstrated that an ac signal of 20 V with frequency range of 500 kHz to 2 MHZ is suitable to remove the tested bacterial population and the rate of removal of E. coli is the highest with a dielectrophoretic filtration efficiency of 77,1%.